Analysis of the sprint start, swimming start and volleyball push off in generating impulse-momentum - Hashem Kilani, H.; Al-Tuieb, M. A.; Kilani, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate the relationship between impulse and change of momentum in three types of ground take-off. Three athletes from the swimming, sprinting and volleyball national teams executed three trials from an AMTI force platform synchronized with video capturing system of starting take-off. APAS software was used for further analysis. Results indicate that the swimmers and the sprinter are less capable of getting equal impulse relationship to the change of momentum due to deviation of reaction forces into the desired motion.